Cultivating Financial Intelligence by Learning to Save and Frugal at an Early Age in Cilandak Village - Nisaul Isti’ani; Didik Himmawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Saving is better taught to children as early as possible even though a family has an excess economic condition. It is better if the science of saving must still be taught to children. Providing education and understanding about the concept of saving must be started and made a habit at an early age because at that moment children are easier to absorb information and have a high curiosity. The moment of financial problems is an opportunity that can be taught to children and adolescents to learn about personal finance and to improve their own financial management skills. The level of awareness, understanding and thinking of children about the importance of living frugally and saving should be known from an early age. This aims to prepare children's understanding to be disciplined in setting aside the money they have and wisely in using the amount of savings someday. The habit of liking to save will have a positive impact on children to appreciate a gift more. The habit of saving can also teach children to live independently. The activity of saving or saving part of the income that is used to meet important and sudden needs for the future. There are many ways to save, for example setting aside pocket money to be saved, limiting snacks so that pocket money can be saved, buying necessary necessities, and so on. However, saving behavior is difficult to implement if it is not taught from an early age so that later when adults it is easy to apply it in everyday life. Saving is an action recommended by Islam, because by saving means a Muslim prepares himself for the implementation of future planning as well as to face unwanted things.